Logics in Action: Managing Institutional Complexity in a Drug Court. (June 2013) - McPherson, Chad Michael; Sauder, Michael
Drawing on a 15-month ethnographic study of a drug court, we investigate how actors from different institutional and professional backgrounds employ logical frameworks in their micro-level interactions and thus how logics affect day-to-day organizational activity. While institutional theory presumes that professionals closely adhere to the logics of their professional groups, we find that actors exercise a great deal of agency in their everyday use of logics, both in terms of which logics they adopt and for what purpose. Available logics closely resemble tools that can be creatively employed by actors to achieve individual and organizational goals. A close analysis of court negotiations allowed us to identify the logics that are available to these actors, show how they are employed, and demonstrate how their use affects the severity of the court's decisions. We examine the ways in which professionals with four distinct logical orientations—the logics of criminal punishment, rehabilitation, community accountability, and efficiency—use logics to negotiate decisions in a drug court. We provide evidence of the discretionary use of these logics, specifying the procedural, definitional, and dispositional constraints that limit actors' discretion and propose an explanation for why professionals stray from their "home" logics and "hijack" the logics of other court actors. Examining these micro-level processes improves our understanding of how local actors use logics to manage institutional complexity, reach consensus, and get the work of the court done.